Model of Ecological Citizenship Program Through Adiwiyata School to Increase Students' Environmental Awareness and Concern at Madrasah Aliyah Negeri 1 Bandung - Edi Kusnadi; Kiki Muhamad Lutfi (Universitas Lambung Mangkurat, 2023)
Environmental awareness and concern are two things that can be a catalyst for the development of Ecological Citizenship in the school environment. This study aims to determine students' level of awareness and concern through the ecological citizenship model program implemented by Madrasah Aliyah Negeri 1 Bandung as the National Adiwiyata School. This study uses a descriptive quantitative approach with questionnaires and interviews. The results showed that students' awareness of the environment showed a very good predicate with a percentage of 84.99%, and students' concern for the environment determined a good predicate with a percentage of 78.28%. Therefore, Madrasah Aliyah Negeri 1 Bandung implemented the ecological citizenship program model through the National Adiwiyata School program to increase students' awareness and concern for the environment.